A Magyarországra irányuló működőtőkét meghatározó tényezők vizsgálata - Katona Klára (2005)
In the 1990s, foreign direct investment played a determining role in world economic development. However, in Central-Eastern Europe and especially in Hungary it was an integral part of the economic transition as well. This study gives a review of the main economic theories and international evidence concerning the determinants of FDI: It analyses how relavant these determinants were in case of Hungary during the 1990s, i.e. what were the main determining factors of FDI-in Hungary. My analysis is based on a regression model. The examined factors are: GDP growth,population, final consumption (market size), import volume (openness), level of privatisation, taxation system, labour cost, labour skills. It turns out clearly that on the long term labour skills was the main determining factor of FDI in Hungary. Therefore I conclude that Hungary's competitive position on world capital markets could be maintained by supporting education and R&D activities.
Keywords: Társadalomtudományok; Közgazdasági és gazdálkodástudományok